Estudio comparativo de bioequivalencia de ocho preparados comerciales de Captopril (1994)
ABSTRACT: In this article is presented a biopharmaceutical evaluation of peak blood levels (plasma concentration) of captopril in 25mg tablets of eight trademarks registres in Colombia. Adesign was set to using a Balanced incomplet block type of experimental design involving 16 patients in a crossed doubled blind trial. The results obtained showed chemical similarities between the eight trademarks used and they reached the peak blood expected in time and concentration in every treatment. On the other hand, could be possible to use with safety in treatments with Captopril, drugs with generic names making the therapy less expensive.